Relationship of Gonadotropin-Releasing Hormones (GnRH) Induction to Reproductive Performance in Batur Sheep - Hidayah, Chomsiatun Nurul; Sumaryadi, M Y; Saleh, D M; Nugroho, A P; Nurasih, A D (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural DevelopmentDO - 10.20884/2.procicma.2023.2.1.7826, 2023)
Experiments were performed to determine the relationship of Gonadotropin-Releasing Hormone (GnRH) induction to estrus activity and pregnancy rate of Batur sheep. Twenty Batur sheep were synchronized to estrus using intramuscularly injection of 2 ml PGF2α that repeated in 11-day intervals. GnRH was given intramuscularly on the 9 th day for 10 Batur sheep, and 10 others were not injected as a control. Reproductive performance included estrus intensity, estrus onset, mating time period, and pregnancy rate. The data were analyzed by regression correlation tests, and chi-square test were used for pregnancy rate. The statistical analysis results showed that the induction of GnRH has a very significant relationship (P<0.01) to the intensity and onset of estrus as well as the time-mating period it has a significant relationship (P<0.05). The pregnancy rate was significantly different (P<0.05) between control and GnRH-induced in Batur sheep. The results showed that GnRH induction contributed to the intensity of estrus, the onset of estrus, and the time-mating period of 37.88, 42.79, and 22.16%, respectively. The pregnancy rate in Batur sheep induced by GnRH compared to controls has 25.0% increased. It can conclude that GnRH induction was able to improve reproductive performance in Batur sheep